Phosphorus Impacts from Meat-, Dairy-, and Plant-Based Diets - Schroeder, Jon (Consilience, 2018)
Phosphorus (P) is a finite resource located within certain geologic reserves around the world. Morocco and the Western Sahara together account for roughly 75% of reserves, raising questions of how to more sustainably use this precious resource. Phosphorus is mined from rock and eventually converted into usable fertilizer, which is applied to croplands. This study aims to contribute to the literature on phosphorus sustainability by analyzing the yearly diet choices of an average American consumer using Life Cycle Assessment (LCA) software. When ascertaining dietary phosphorus use, meat- and plant-based diets have traditionally been juxtaposed. Using data from the United Nations and a study by a consulting firm in Boston, the LCA queries through the food materials that meat-based, dairy-based, and plant-based diets contain, and yields a rough estimate of total P consumption in kilograms. Findings show that as anticipated, a meat-based diet is higher in P consumption than a dairy-based or plant-based diet and gives credence to the notion that consumers in their everyday lives can affect the sustainable use of scarce resources such as phosphorus. Concluding this report is a brief discussion summarizing literature findings on how to use P more sustainably in other sectors, such as wastewater treatment.